Distributed adaptive output feedback consensus protocols for linear systems on directed graphs with a leader of bounded input. (December 2016) - Lv, Yuezu; Li, Zhongkui; Duan, Zhisheng; Chen, Jie
Abstract: This paper studies output feedback consensus protocol design problems for linear multi-agent systems with directed graphs containing a leader whose control input is nonzero and bounded. We present novel distributed adaptive output feedback protocols to achieve leader–follower consensus for any directed graph containing a directed spanning tree with the leader as the root. The proposed protocols are independent of any global information of the graph and can be constructed as long as the agents are stabilizable and detectable.